2018
DOI: 10.1039/c8sc02406e
|View full text |Cite
|
Sign up to set email alerts
|

Can percolation theory explain the gelation behavior of diblock copolymer worms?

Abstract: Physical gelation by block copolymer worms can be explained in terms of multiple inter-worm contacts using percolation theory, suggesting that worm entanglements are irrelevant in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
127
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 72 publications
(137 citation statements)
references
References 76 publications
10
127
0
Order By: Relevance
“…This indicates the formation of highly anisotropic worms, with multiple inter-particle contacts producing a 3D network. 56 The storage modulus (G 0 ) exceeds the loss modulus (G 00 ) at 17 C, which corresponds to the critical gelation temperature (CGT) (Fig. S3, ESI, † for G 0 and G 00 data).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates the formation of highly anisotropic worms, with multiple inter-particle contacts producing a 3D network. 56 The storage modulus (G 0 ) exceeds the loss modulus (G 00 ) at 17 C, which corresponds to the critical gelation temperature (CGT) (Fig. S3, ESI, † for G 0 and G 00 data).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of varying L c on gel strength has also been observed for surfactant worms 78 and has been recently rationalized in the context of percolation theory for this particular polymer formulation by Lovett and co-workers. 53 …”
Section: Resultsmentioning
confidence: 99%
“… 28 , 51 , 52 In each case, free-standing gels can be obtained above a certain critical copolymer concentration known as the critical gelation concentration (CGT). 53 Moreover, such worm gels can exhibit interesting thermoresponsive behavior: adjusting the solution temperature leads to a worm-to-sphere transition, which leads to in situ degelation. 8 , 21 , 28 , 32 , 47 For example, poly(glycerol monomethacrylate)–poly(2-hydroxypropyl methacrylate) (PGMA–PHPMA) diblock copolymer worm gels undergo degelation on cooling from 20 to 5 °C.…”
Section: Introductionmentioning
confidence: 99%
“…This convenient synthetic route allows for the direct derivatization of epoxy-containing diblock copolymer worms with 4-amino-TEMPO to give nitroxidefunctionalized diblock copolymer worms. Owing to their highly anisotropic nature, such diblock copolymer worms are expected to form a percolating network at relatively low volume fractions 32 and hence may exhibit superior charge transport properties. [9][10] Synthesis of diblock copolymer worms from GlyMA An initial aqueous emulsion of GlyMA was converted into an aqueous solution of GMA by heating at 85 °C for 9 h. 33 1 H NMR analysis indicated that the conversion of GlyMA to GMA was approximately 98%, see Fig.…”
Section: Resultsmentioning
confidence: 99%